2018
DOI: 10.1515/folmed-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid in Pertrochanteric Femoral Fracture: Is it a Safe Drug or Not?

Abstract: Based on this study, the use of tranexamic acid was statistically significant in reducing post-surgery blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 34 publications
1
33
1
Order By: Relevance
“…Despite the wide use of TXA, there has been concern regarding its association with increased incidence of venous thrombosis and mortality. 32 Zufferey et al 17 and Schiavone et al 36 reported a three-fold increase in vascular events (deep venous thrombosis, pulmonary embolism, cerebrovascular accident, and myocardial infarction) with intravenous TXA administration in hip fracture surgery, but this was not statistically significant. A number of metaanalyses have found no increase in thromboembolic complications but were unable to draw conclusions regarding the safety of TXA because of potential bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wide use of TXA, there has been concern regarding its association with increased incidence of venous thrombosis and mortality. 32 Zufferey et al 17 and Schiavone et al 36 reported a three-fold increase in vascular events (deep venous thrombosis, pulmonary embolism, cerebrovascular accident, and myocardial infarction) with intravenous TXA administration in hip fracture surgery, but this was not statistically significant. A number of metaanalyses have found no increase in thromboembolic complications but were unable to draw conclusions regarding the safety of TXA because of potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of previous studies. 33,34 Gausden et al 35 and Schiavone et al 36 reported significant reductions in transfusion rates with TXA use versus placebo. In the TXA in Hip Fracture Surgery study, Zufferey et al 17 also reported the same trend with a 30% relative reduction in transfusion rates with TXA administration.…”
Section: Discussionmentioning
confidence: 99%
“…After a detailed evaluation, eight independent RCTs[10,23,30-35] with cumulatively 836 patients were included in the overall meta-analysis (Figure 1). Most of the RCTs were relatively well-designed and their CONSORT adherence scores ranged from 19 to 24, with a maximum score of 25.…”
Section: Resultsmentioning
confidence: 99%
“…There are studies in the literature investigating the effects of some protocols on blood loss following femoral fracture surgery. Schiavone et al reported that the use of tranexamic acid significantly decreased the amount of postsurgery blood loss and thus the need for transfusion in the surgical treatment of femoral fractures [26]. However, since our primary objective was to investigate the AB0 blood system, we did not evaluate the effects of such protocols.…”
Section: Discussionmentioning
confidence: 98%